Effects of physical training on sarcomere lengths and muscle-tendon interface of the cervical region in an experimental model of menopause - Jacob, Carolina dos Santos [UNESP]; Rocha, Lara Caetano [UNESP]; Pimentel Neto, Jurandyr [UNESP]; Watanabe, Ii-Sei; Ciena, Adriano Polican [UNESP] (Pagepress Publ, 2019)
The aim of this study was to describe the structural and ultrastructural aspects of the myotendinous junction (MTJ) and the proximal and distal sarcomeres of the sternomastoid of aged Wistar rats subjected to an experimental model of menopause and swimming training. A total of 20 female elderly rats were divided into the following four groups (n = 5 in each group): sedentary/no-menopausal (SNM), trained/nomenopausal (TNM), sedentary/menopausal (SM), and trained/menopausal (TM). The MTJ samples were dissected and analyzed using transmission electron microscopy. We showed that the TNM Group rats exhibited changes in morphological characteristics as a consequence of physical exercise, which included an increase of 36.60% (P<0.001) in the evagination length of the MTJ and a reduction in the length of the distal (77.38%) (P<0.0001) and proximal (68.15%) (P<0.0001) sarcomeres. The SM Group exhibited a reduction of about 275.93% (P<0.001) in the muscle-tendon interface and in the lengths of distal sarcomeres (55.87%) (P<0.0001) compared with SNM Group. Our results suggest that the swimming training under experimental model of menopause promoted tissue reorganization and increased muscle-tendon interaction with a drastic development in the length and thickness of the sarcoplasmatic invaginations and evaginations. In addition, the sarcomeres exhibited different lengths and a reduction in both groups subjected to swimming training.
Keywords: Sarcomere; myotendinous junction; menopause model; aging; physical exercise